Comparison of Auscultation Method Versus Lung Ultrasound Technique to Evaluate the Accuracy of Positioning of Left Double Lumen Tube in Patients Undergoing Cardiothoracic Surgery - Agarwal, Swati; Verma, Indu; Sharma, Jai; Dagar, Nivedita (Indonesian Journal of Anesthesiology and Reanimation, 2024)
Introduction: Cardiothoracic surgery is a complex and highly specialized medical field requiring precise surgical techniques and meticulous patient management. One critical aspect of this type of surgery is the accurate placement of the endobronchial double-lumen tube (DLT), which facilitates lung isolation and one-lung ventilation (OLV) during the procedure. Proper positioning of the DLT is essential to ensure adequate oxygenation, prevent complications, and optimize surgical access. Objective: This study aimed to compare the accuracy of positioning of the left DLT by the auscultation method versus the lung ultrasound technique in patients undergoing cardiothoracic surgery in both supine and lateral positions. Methods: A prospective, observational, and cross-sectional study was conducted in a single group of 62 patients based on the eligibility criteria. After general anesthesia, a DLT was inserted and rotated until resistance. Placement was confirmed by auscultation, ultrasound, and fibreoptic bronchoscopy. The evaluation process was done initially in a supine position, followed by a lateral position. Results: After insertion of the left DLT, initially evaluated in the supine position, sensitivity and specificity for auscultation were found to be 65.2% and 37.5%, respectively, sensitivity and specificity for ultrasonography were 82.6% and 75%, respectively. The accuracy of lung ultrasound at 80.7% (69.2%-88.6%) was higher than the accuracy of auscultation at 58.1% (45.7%-69.5%). This was followed by evaluation in lateral position, where sensitivity and specificity for auscultation were found to be 76.1% and 25% respectively, sensitivity and specificity for ultrasonography were 95.7% and 62.5%, respectively. The accuracy of lung ultrasound at 87.1% (76.6%-93.3%) was higher than the accuracy of auscultation at 62.9% (50.5%- 73.8%). Conclusion: Lung ultrasound is a superior method for assessing lung isolation and determining Double Lumen Tube position as compared to auscultation.